Cheesecake-eating rats and the question of food addiction - Epstein, David H (2010)
Rats given extended access to high-fat high-sugar food show behavioral and physiological changes that are similar to those caused by drugs of abuse. However, parallels between drug and food “addiction” should be drawn with caution.